PPTS Inhibits the TGF-β1-Induced Epithelial-Mesenchymal Transition in Human Colorectal Cancer SW480 Cells. (22nd September 2019) - Zhang, Ling; Naeem, Abid; Wei, Shaofeng; Li, Zexie; Zang, Zhenzhong; Wang, Meng; Liu, Yali; Su, Dan
Abstract : The current study investigates the inhibitory effects of Pulsatilla pentacyclic triterpenoid saponins extract (PPTS) on epithelial-mesenchymal transition (EMT) triggered by the transforming growth factor- β 1 (TGF- β 1) in human colorectal cancer SW480 cell line, further illustrates the possible mechanism of PPTS inhibition of growth and invasion from the perspective of EMT, and provides new theoretical support for the treatment of tumor by Chinese medicine. The SW480 cells were treated in groups: blank control, TGF- β 1 (10 ng/mL), and varying concentrations of PPTS cotreated with TGF- β 1-induced (10 ng/mL) groups. CCK8 was used to detect cell viability; transwell was applied to detect invasion ability, cell migration ability was also determined, ELISA and RT-qPCR were utilized for the determination of CYP3A, CYP2C9, CYP2C19, N-cadherin, and MMP-9 expression. Flow cytometry detection was applied to detect cell cycle and apoptosis. The results obtained have shown that PPTS can significantly inhibit the invasion and migration of tumors in SW480 cells and can also block the S phase in the cell cycle but may produce cytotoxicity in higher doses. The present research work provides substantial evidence that PPTS has a significant inhibitory effect on TGF- β 1-induced EMT in SW480 cells and it also promotes apoptosis.